2023
DOI: 10.1002/apxr.202200095
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Local Conductance to Enable Demonstrator Ferroelectric Domain Wall Diodes and Logic Gates

Abstract: Fundamentally, lithium niobate is a good electrical insulator. However, this can change dramatically when 180°domain walls are present, as they are often found to be strongly conducting. Conductivities depend on the inclination angles of walls with respect to the polarization axis and so, if these angles can be altered, then electrical conduction can be tuned, or toggled on and off. In ≈500 nm thick z-cut ion-sliced thin films, localized wall angle variations can be controlled by both the sense and magnitude o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The extracted values of the forward and backward diode ideality factors, which are n f = 23 and n b = 76, were a surprise in comparison to the single-crystal results, where n f appears to be systematically larger than n b . Thus, the data might indicate a different mechanism responsible for the directional asymmetry in the thin-film sample, which is supported by the findings by Suna et al [20] showing that near-surface DW bending results in a significant contribution to the diode like response. Nevertheless, an in-depth clarification needs a more systematic approach, which is outside the scope of the present study.…”
Section: Applying the R2d2 Model To Domain Wall Conductance In Thin-f...supporting
confidence: 83%
See 1 more Smart Citation
“…The extracted values of the forward and backward diode ideality factors, which are n f = 23 and n b = 76, were a surprise in comparison to the single-crystal results, where n f appears to be systematically larger than n b . Thus, the data might indicate a different mechanism responsible for the directional asymmetry in the thin-film sample, which is supported by the findings by Suna et al [20] showing that near-surface DW bending results in a significant contribution to the diode like response. Nevertheless, an in-depth clarification needs a more systematic approach, which is outside the scope of the present study.…”
Section: Applying the R2d2 Model To Domain Wall Conductance In Thin-f...supporting
confidence: 83%
“…The enormous scientific interest is reflected in several review articles treating fundamental [4][5][6] and technological [7][8][9] challenges in understanding and exploiting this type of quasi-two-dimensionally confined electronic transport, which competes with other highly topical low-dimensional electronic systems like graphene, oxide samples, albeit for a rather narrow temperature range so far [10,12,[15][16][17]. In parallel, there are a plethora of very recent application-related results already demonstrating single electronic DW-based functionality in either LNO single crystals or thin films, ranging from simple rectifying junctions [12,[18][19][20] to more complex logic gates [20,21], memristors [22,23], and transistors [21,24,25], to name just a few.…”
Section: Introductionmentioning
confidence: 99%
“…Exploiting these multi-level interfacial wall diodes in three-terminal mesa-like devices based on LiNbO 3 (figure 2(d)), the logic gate functionality of NOT, NAND, and NOR was demonstrated, which is crucial for the development of logic-in-memory computing [108]. In a different methodology, a diode-like transport behaviour was also achieved through a stable control of near-surface wall topology or inclination in LiNbO 3 [110]. These wall diodes were used to construct and show AND and OR logic gates.…”
Section: Multi-level Solid-state Wall Devicesmentioning
confidence: 99%
“…Importantly, logic gate functions such as NOT, NOR, and NAND (Figure 4c) are implemented in a cascade manner using the in-plane domain wall as the transmission medium. 140 Using vertical LiNbO 3 capacitor structure, Suna et al 141 also showed domain wall diode functionality and constructed the AND and OR gates through control of walls inclination and hence charge state (Figure 4d).…”
Section: Field-effect Devices Logic Gates and In-memory Computingmentioning
confidence: 99%